Advanced oral drug delivery systems for gastrointestinal targeted delivery: the design principles and foundations - Yafei Zhang; Yiran Wang; Yao Lu; Heng Quan; Yuqi Wang; Sijia Song; Huiyuan Guo (Journal of Nanobiotechnology)
Abstract Oral administration has long been considered the most convenient method of drug delivery, requiring minimal expertise and invasiveness. Unlike injections, it avoids discomfort, wound infections, and complications, leading to higher patient compliance. However, the effectiveness of oral delivery is often hindered by the harsh biological barriers of the gastrointestinal tract, which limit the bioaccessibility and bioavailability of drugs. The development of oral drug delivery systems (ODDSs) represents a critical area for the advancement of pharmacotherapy. This review highlights the characteristics and precise targeting mechanisms of ODDSs. It first examines the unique properties of each gastrointestinal compartment, including the stomach, small intestine, intestinal mucus, intestinal epithelial barrier, and colon. Based on these features, it outlines the targeting strategies and design principles for ODDSs aimed at overcoming gastrointestinal barriers to enhance disease treatment. Lastly, the review discusses the challenges and potential future directions for ODDS development, emphasizing their importance for advancing drug delivery technologies and accelerating their future growth. Graphical Abstract